Case Report: Interest of Positron Emission Tomography in Pediatric Small Vessel Primary Angiitis of the Central Nervous System - Belcour, Morgane; Dontaine, Pauline; Monier, Anne; Lebrun, Laetitia; Salmon, Isabelle; De Witte, Olivier; Goldman, Serge; De Tiège, Xavier; Aeby, Alec (Frontiers in Pediatrics, 2022)
Primary angiitis of the central nervous system (PACNS) is a rare inflammatory disease affecting central nervous system vessels. The diagnosis, which requires confirmation by brain biopsy, remains challenging due to unspecific clinical presentation and low specificity of imaging and laboratory exams. In these two pediatric biopsy-proven cases of svPACNS we demonstrate that brain positron emission tomography (PET) show a high metabolic activity that extends beyond brain MRI abnormalities. Therefore, combining MRI and PET abnormalities to adequately guide brain biopsy might increase the diagnostic yield of this rare condition.